Jovenes Fotografos 1989. - Salaamadis, Madrid (Madrid : Instituto de la Juventud, 1989)
Abalo, José Luis ; Bianco, Antonio ; Contreras, Luis ; Freire, Francisco José ; Gómez, Maria José ; Herraiz, Alfonso ; Laorden, Fernando ; Charris, Angel Mateos ; Mollá, Javier ; Mosquera, Rodrigo ; Nazábal, Juan ; Ochoa, José Julián ; Ruiz, Silvia ; Valverde, Guillermo ; Vargas, Rafael
Jovenes Fotografos 1989, Salaamadis, Madrid, del 28 de junio al 16 de septiembre 1989
boek